Diseño de gestión en control de un sistema de seguridad y salud ocupacional para una empresa encargada de la distribución y el mantenimiento del agua potable - Viteri, Marcelo Mauricio (2011)
The organization that is under study is devoted to ensure the quality of water drawn from underground wells, analysis of the water regularly and chlorination of the same to eliminate bacteria or micro-organisms that may affect the health of users, in addition guarantee efficient distribution of vital liquid conducting periodic maintenance to the pumps, wells, reservoirs and control panels, with the aim of the user is water continuously. Analyzes the general information of the company and its productive process, described the characteristics of the facilities, equipment and tools that are used to the realization of the day. In addition is analyzed the current situation of the organization with regard to the safety and health at work, and then analyze the tasks in order to evaluate them and determine the activities of greater risk. On this basis is designed the System, in which are established control measures, is a training plan according to the needs of training identified, was establishing procedures for the hazard identification and assessment of risks, and establish parameters of performance measurement of the system in order to continuously improve. Finally, we present the conclusions and recommendations for implementing the system, which seeks to strengthen the organizational aspects of occupational health and safety which will reduce risks in their operations.